فعالية الإتصال الداخلي في المؤسسة دراسة ميدانية لمجموعة BIOCARE لتصنيع الأدوية- بن مهيدي- ولاية الطارف - درايعية أسماء (My University, 2019)
Abstract : In this study, we sought to identify the effectiveness of internal communication in the organization and its impact on increasing the employees' self-awareness through the access of the information in terms of the means and techniques used in communicating messages, the nature of these messages and the content of the message, All this through the exploitation of various means and methods as well as communication messages. And finally, the participation of employees and involving them in the decisions of the institution. This study raises a specific problematic surrounding a major question: How effective is the internal communication system of Biocare laboratories is in creating employee awareness? Using the questionnaire, the interview and simple observation as data collection tools, with our reliance on the sample survey methodology that is included in the descriptive studies, we found that the institution was unable to provide briefings and information concerning the employees. However, in general, it succeeded in communicating this information in a timely manner, using clear messages through appropriate means of communication. ------------------------ ملخص: سعينا في هذه الدراسة إلى تحديد مدى فعالية الاتصال الداخلي في المؤسسة وأثره في زيادة الوعي الذاتي لدى الموظفين من خلال الوصول إلى المعلومات، من حيث الوسائل والتقنيات المستخدمة في إيصال الرسائل، وطبيعة هذه الرسائل، ومضمونها، وذلك من خلال توظيف مختلف الوسائل والأساليب، بالإضافة إلى رسائل الاتصال. وأخيرًا، مشاركة الموظفين وإشراكهم في اتخاذ قرارات المؤسسة. وتطرح هذه الدراسة إشكالية محددة تتمحور حول سؤال رئيسي: ما مدى فعالية نظام الاتصال الداخلي في مختبرات بيوكير في خلق وعي الموظفين؟ باستخدام الاستبيان والمقابلة والملاحظة البسيطة كأدوات لجمع البيانات، واعتمادنا على منهجية مسح العينة المضمنة في الدراسات الوصفية، وجدنا أن المؤسسة لم تتمكن من تقديم إحاطات ومعلومات تخص الموظفين. ومع ذلك، فقد نجحت بشكل عام في إيصال هذه المعلومات في الوقت المناسب، باستخدام رسائل واضحة من خلال وسائل اتصال مناسبة.
Keywords: فعالية الإتصال الداخلي، المؤسسة